ANALISIS PERKEMBANGAN LIKUIDITAS DAN RENTABILITAS PADA CV. MENDIHO - Jasasila Jasasila (Universitas Batanghari Jambi, 2018)
The purpose of this research is to know and analyze the development of Liquidity and Rentability tingat on CV. Mendiho 2012-2016, the analysis used to see the level of Liquidity indicator used: Curent Ratio¸ Quick Ratio and Cash Ratio while for Rentability used indicator: Net Profit Margin, Return on Investment and Return On Equity. From the analysis results obtained that CV. Mendiho is able to meet its short-term liabilities (Liquidity) with the average of each indicator: Curent Ratio 555.46%, Quick Ratio (450.93%) and Cash Ratio (299.94%), which is above average which has been set, although the developments that occur for each indicator is very volatile. For Rentability CV. Mendiho is also able to obtain maximum profitability (Rentability), with each indicator average: Net Profit Margin with average 51.17%, Return On Investment (90.06%) and Return On Equty (544,53 %) and developments for each indicator are also very volatile.Keywords: Liquidity, Profitability